فيزياء الشبكة العصبية ونظام الذاكرات اللامحدود في خلائط نظام الزجاج السبيني (Latakia University Journal -Basic Sciences Series, 2018)
Theoretical neural network model has been proposed, to simulate a model derived from theory of spin glass, which stress on hierarchical regime used in neural network and the genetic theory of generational succession and communication with each other. Hamiltonian energy has been adapted to comparison between the neural network and hierarchical regime in spin glass alloys. The study emphasizes that the computer which have boundless capacity and mimics the human brain, can be produced through the developing of this kinds of spin glass alloys.تم اقتراح نموذج نظري للشبكة العصبية يحاكي النموذج المستنبط من نظرية الزجاج السبيني الذي يؤكد على النظام التفرعي المستخدم في الشبكة العصبية و في النظرية الوراثية لتعاقب الأجيال واتصالها مع بعضها البعض. وقد تم اعتماد هاملتون الطاقة للمقارنة بين الشبكة العصبية والنظام التفرعي في خلائط الزجاج السبيني ، تؤكد الدراسة على أن الحاسوب الذي سوف يتمتع بالسعة اللامحدودة ويحاكي الدماغ البشري سيكون عبر تطوير خلائط الزجاج السبيني.